2009
DOI: 10.1007/s10237-009-0166-1
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of single chondrocytes under direct shear

Abstract: Articular chondrocytes experience a variety of mechanical stimuli during daily activity. One such stimulus, direct shear, is known to affect chondrocyte homeostasis and induce catabolic or anabolic pathways. Understanding how single chondrocytes respond biomechanically and morphologically to various levels of applied shear is an important first step toward elucidating tissue level responses and disease etiology. To this end, a novel videocapture method was developed in this study to examine the effect of direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…a unique set of passive material properties cannot be identified for a cell. The significant contribution of the actin cytoskeleton to the mechanical response of cells has been demonstrated in numerous experimental studies [17,18]. It has recently been demonstrated that a computational cell model must include the key features of remodelling and contractility of the actin cytoskeleton in order to provide a realistic prediction of cell biomechanical response to physical stimuli [18][19][20][21][22].…”
Section: Previous Studies Have Assumed Simple Viscoelastic Constitutimentioning
confidence: 99%
“…a unique set of passive material properties cannot be identified for a cell. The significant contribution of the actin cytoskeleton to the mechanical response of cells has been demonstrated in numerous experimental studies [17,18]. It has recently been demonstrated that a computational cell model must include the key features of remodelling and contractility of the actin cytoskeleton in order to provide a realistic prediction of cell biomechanical response to physical stimuli [18][19][20][21][22].…”
Section: Previous Studies Have Assumed Simple Viscoelastic Constitutimentioning
confidence: 99%
“…The glass substrate containing the cells was then placed in a Petri dish on an inverted microscope. A shear deformation was applied to individual cells by a tungsten probe [22]. Initially, the probe was positioned adjacent to the cell, 4 mm above the substrate (figure 1a).…”
Section: Experimental Methodsmentioning
confidence: 99%
“…These microarrays have been used to study the adhesion and contractility of static cells [8,10] cells subjected to local [11] and global applied deformation [12], cell migration [13,14], and cell -cell adhesion [15]. Micropost arrays provide detailed quantitative data about the contractility of cells and measure tractions at a number of points on the cell [8], in contrast to whole-cell measurements obtained from atomic force microscopy or cell probing [16][17][18]. Numerous different designs of these arrays exist, with variations in the length and diameter of the pillars, the spacing between pillars, and the arrangement in square or triangular patterns.…”
Section: Introductionmentioning
confidence: 99%